2011
DOI: 10.1097/coc.0b013e3181e84dc0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tumor Volume and Radiotherapy Dose on Outcome in Previously Irradiated Recurrent Squamous Cell Carcinoma of the Head and Neck Treated With Stereotactic Body Radiation Therapy

Abstract: Purpose To assess the effect of stereotactic body radiotherapy (SBRT) dose and tumor volume on outcomes in patients with recurrent, previously irradiated squamous cell carcinoma of the head and neck. Materials and Methods A total of 96 patients with recurrent, previously irradiated squamous cell carcinoma of the head and neck were treated with SBRT using Cyberknife and Trilogy-intensity-modulated radiosurgery. Kaplan-Meier survival analyses were used to estimate locoregional control (LRC) and overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 42 publications
10
94
1
1
Order By: Relevance
“…In addition to disease-related factors, current comorbidities, age, and also the individual expectations of the patient and preexisting organ dysfunction have to be taken into account when selecting patients for reirradiation. Similarly, on unplanned subgroup analyses we validate the previously established importance of tumor volume < 25cc and present hypothesis-generating trends for the potential impact of re-challenging patients with cetuximab containing regimens who have failed a prior EGFR inhibitor (18). Limiting the SBRT treatment volume to the GTV, the 1-year local PFS was 60%, and the 1-year locoregional PFS was 37%; prior patterns of failure from IMRT series have supported a similar focus on the recurrence GTV, but this pattern begins to highlight the competing risk of locoregional failure especially given the 36% risk of failure in the uninvolved neck in patients treated for nodal recurrence (32).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In addition to disease-related factors, current comorbidities, age, and also the individual expectations of the patient and preexisting organ dysfunction have to be taken into account when selecting patients for reirradiation. Similarly, on unplanned subgroup analyses we validate the previously established importance of tumor volume < 25cc and present hypothesis-generating trends for the potential impact of re-challenging patients with cetuximab containing regimens who have failed a prior EGFR inhibitor (18). Limiting the SBRT treatment volume to the GTV, the 1-year local PFS was 60%, and the 1-year locoregional PFS was 37%; prior patterns of failure from IMRT series have supported a similar focus on the recurrence GTV, but this pattern begins to highlight the competing risk of locoregional failure especially given the 36% risk of failure in the uninvolved neck in patients treated for nodal recurrence (32).…”
Section: Discussionsupporting
confidence: 60%
“…Later, based on a patterns-of-failure analysis, the protocol was amended to allow a 3-ot 5-mm PTV expansion on the GTV (17). Tumors <25 cm 3 received 8.0 Gy per fraction for 5 fractions to 40 Gy; tumors !25 cm 3 received 8.8 Gy per fractions for 5 fractions to 44 Gy (18). SBRT was delivered on alternating days on an outpatient basis over 1 to 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have indicated the usefulness of these new techniques for the management of head and neck tumors [13][14][15][16][17][18]. The CyberKnife system is a robotic stereotactic radiosurgery/radiotherapy device that can deliver a high dose of radiation precisely and with minimal damage to surrounding tissue [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The University of Pittsburgh experience suggests a dose response with a trend toward improved survival with doses of 40 Gy or higher. (27) However, none of these studies reported Monte Carlo-computed dose distributions for the head and neck SRT patients. Our retrospective study demonstrated the feasibility of using Monte Carlo-based treatment planning and dose calculation for clinical head and neck SRT patients.…”
Section: Discussionmentioning
confidence: 99%